Sterically demanding AgI and CuI N-heterocyclic carbene complexes: synthesis, structures, steric parameters, and catalytic activity - Cervantes Reyes, Alejandro; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2020)
Abstract The synthesis and full characterization of new air-stable AgI and CuI complexes bearing structurally bulky expanded-ring N-heterocyclic carbene (erNHC) ligands is presented.